2014
DOI: 10.1093/hmg/ddu461
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of SLC9A1, encoding the major Na+/H+ exchanger, causes ataxia-deafness Lichtenstein-Knorr syndrome

Abstract: Lichtenstein-Knorr syndrome is an autosomal recessive condition that associates sensorineural hearing loss and cerebellar ataxia. Here, we report the first identification of a gene involved in Lichtenstein-Knorr syndrome. By using a combination of homozygosity mapping and whole-exome sequencing, we identified the homozygous p.Gly305Arg missense mutation in SLC9A1 that segregates with the disease in a large consanguineous family. Mutant glycine 305 is a highly conserved amino acid present in the eighth transmem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…AP1 cells were transiently transfected with wild type HA-tagged NHE1 cDNA [7]. Proteins present at the cell surface were labeled with sulfo-NHS-SS-biotin as described earlier [18] and immobilized streptavidin resin was used to remove cell surface labeled protein.…”
Section: Characterization Of Glycosylationmentioning
confidence: 99%
See 2 more Smart Citations
“…AP1 cells were transiently transfected with wild type HA-tagged NHE1 cDNA [7]. Proteins present at the cell surface were labeled with sulfo-NHS-SS-biotin as described earlier [18] and immobilized streptavidin resin was used to remove cell surface labeled protein.…”
Section: Characterization Of Glycosylationmentioning
confidence: 99%
“…NHE1 also plays a clear role in mammalian development. Mice with a NHE1 deletion have decreased postnatal growth and increased mortality, ataxia and epileptic seizures [6] and we have recently demonstrated that homozygous expression of a defective NHE1 gene in humans results in disease, with a phenotype including hearing loss and cerebellar ataxia [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human NHE1 mutations had not been identified until recently, when a non-synonymous Gly305Arg substitution was shown to cause Lichtenstein-Knorr syndrome, a rare, autosomal recessive disorder characterized by ataxia and neurosensory deafness, with onset of symptoms typically by 1–2 years of age [157]. The mutation removes a critical NHE1 glycosylation site, resulting in loss of NHE1 targeting to the plasma membrane and a consequent absence of NHE1 Na + –H + exchange activity.…”
Section: Nhe1 Function At the Systemic Levelmentioning
confidence: 99%
“…Mutations were found in WWOX in two families with childhood-onset HCA, generalised tonic-clonic epilepsy and mental retardation (SCAR12); while the knock-out mice present spontaneous and audiogenic seizures as well as balance disturbances [20]. In a family with ataxia and sensorineural hearing loss, a homozygous mutation in SLC9A1 was identified; in the spontaneous swe mutant mice, degeneration of deep cerebellar, vestibular and cochlear nuclei is reported [21]. In GRID2, loss-of-function mutations have been described in early-onset ataxia phenotypes with various accompanying symptoms, concordantly with hotfoot mice [22][23][24].…”
Section: A Bumper Harvest Of Novel Genesmentioning
confidence: 99%